Early Introduction of Emotions: CERIA Program to Develop Children's Emotional Intelligence with Storytelling Methods - Dyan Prastika, Netty; Rahayu, Diah; Purwanti, Silviana (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
The early introduction of emotions is an important step in supporting children's psychological development. However, many young children still struggle to recognize and express their emotions appropriately. The lack of effective methods in emotional education within school environments remains a challenge that needs to be addressed. The community service program